2010
DOI: 10.4236/jmmce.2010.97047
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of High Temperature Wear Resistance of AISI 316 ASS through NiCrBSiCFe Plasma Spray Coating

Abstract: In this work, the microstructural description, mechanical properties and dry

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 20 publications
(26 reference statements)
1
7
0
Order By: Relevance
“…Five temperature levels were used, from room temperature to 570°C, as shown in Table 3. The amount of material removal was calculated from the difference in mass of the pins before and after the tests, using Precisa XB 220 A balance with an accuracy of 0.0001 g. Volumetric wear was calculated by subtracting the mass of the pin before and after testing and dividing it by the density of the stainless steel, (Parthasarathi and Duraiselvam, 2010).…”
Section: -2: Wear Testmentioning
confidence: 99%
See 1 more Smart Citation
“…Five temperature levels were used, from room temperature to 570°C, as shown in Table 3. The amount of material removal was calculated from the difference in mass of the pins before and after the tests, using Precisa XB 220 A balance with an accuracy of 0.0001 g. Volumetric wear was calculated by subtracting the mass of the pin before and after testing and dividing it by the density of the stainless steel, (Parthasarathi and Duraiselvam, 2010).…”
Section: -2: Wear Testmentioning
confidence: 99%
“…They found that the wear increased from room temperature to 350°C and then decreased significantly up to 650°C, due to the formation of different types of oxides. Parthasarathi (Parthasarathi and Duraiselvam, 2010) studied the wear rate of austenitic stainless steel at high temperatures and claimed that the oxide layer began to form at 350°C and more, which protected the surface from the wear. Kennedy (Kennedy, Lu and Baker, 2015) studied the temperature of contact surfaces and proved that the temperature arises in sliding contact surfaces and is the summation of the ambient temperature, the temperature rise due to friction, and the flash temperature that occurs at the localized contact points.…”
Section: Introductionmentioning
confidence: 99%
“…By using these techniques, the amorphous coatings are prepared by melting the feedstock particles into droplets, impinging the droplets onto a cold substrate and forming the coatings by rapid solidification in situ. Previous works have reported that NiCrBSi-based thermally sprayed coatings containing amorphous structures exhibit high hardness and wear-corrosion resistance [18,19]. Planche et al compared the characteristics of the NiCrBSi coatings sprayed by using plasma, flame and HVOF processes [20].…”
Section: Introductionmentioning
confidence: 99%
“…Author has optimised the process parameters for both chromium carbide and titanium carbide surface alloying treatments, so that improvement of the sliding wear resistance of AISI 316L stainless steel may occur without any ill effect on high temperature oxidation resistance. Coatings have been used widely to improve the wear resistance of the stainless steels [13][14][15][16][17][18][19][20][21]. Parthasarathiet.…”
Section: Introductionmentioning
confidence: 99%
“…al. [14] have used plasma sprayed NiCrBSiCFe coatings and established that the wear performance of AISI 316 has increasedby almost 4-5 times as compared to the bare substrate. In another study, the Cr-C-O composite coatings were developed on AISI 304 stainless steel by using cathodic vacuum arc deposition (CVAD) technique.…”
Section: Introductionmentioning
confidence: 99%